Родовища та показники якості бурого вугілля України - Мірошниченко, Денис Вікторович; Пиш'єв, Сергій Вікторович; Лисенко, Людмила Анатоліївна (ТОВ "Гнозіс", 2024)
On the territory of Ukraine, brown coal deposits are associated with various types of geological structures: Ukrainian crystalline shield (Dnieper Basin); Dnipro-Donetsk depression; Volyn-Podilsky plate (Prydniester coalfield); depressions (Prykarpatska and Zakarpatska coal-bearing areas); depressions in Neogene sediments (NizhnyDniester area); a number of coal deposits are found in the mountainous part of the Crimea. The lignite deposits of the western regions of Ukraine are characterized by coal bearing, which is confined to Neogene deposits. There are three coal-bearing areas in this territory: Transnistria, Prykarpatska and Transcarpathia. Layers of lignite in these areas are thin, rarely reaching 1–2 meters. The resources of the area are classified as unpromising, only the Ilnytsk deposit in Transcarpathia is developed by industry [3]. As of January 1, 2021, the number of deposits in Ukraine is 80, of which 3 are being developed. The balance reserves of lignite in Ukraine are: – categories A+B+C1 – 2593359.00 thousand tons; – category C2 – 299,181.00 thousand tons. Тhe largest deposits of brown coal of categories A+B+C1 in Ukraine are located in Dnipropetrovsk (1320,644,00 thousand tons), Kirovohrad (750,833,00 thousand tons), and Kharkiv (389,985,00 thousand tons) regions. Some quality indicators were calculated according to the formulas given in the periodical scientific literature and based on our own analyzes of lignite. Lignite reserves of Ukraine were estimated using Ukrainian and international lignite classifications. Data on reserves and indicators of the quality of lignite of Ukraine were taken from the website of the State Scientific and Production Enterprise «State Geological Information Fund of Ukraine». Among the existing classifications, the most suitable for the distribution of lignite of Ukraine is the International code system of lignite, which is regulated in ISO 2950:1974 «Brown coal and lignites – Classification by types on the basis of total moisture content and tar yield».
Keywords: родовища; вугілля; буре вугілля; вугільна галузь; енергія; буровугільні басейни